Effect of fiber reinforcement on mixed-mode fracture of polymer mortars. (1st May 2016) - Moreira, G.C.; Reis, J.M.L.; Rohan, U.; Soares, C.A.P.; da Costa Mattos, H.S.
Abstract: The present paper is concerned with the failure analysis of cracked polymer mortar reinforced with particles from waste Tetra Pak® aseptic carton packages, piassava lees and glass fiber in combined mode I and II. The Brazilian disk, a classic mixed mode fracture test specimen, was adopted for the experimental characterization of the crack initiation. A slight increase in critical stress intensity factors was observed with the addition of carton particles and piassava lees. Glass fiber reinforcement promotes the highest fracture resistance to crack propagation.